Social Media, Price Perception, and Repurchase Intention: The Role of Trust - Menhard; Syafwandi; Yulasmi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This research examines the influence of Social Media Marketing (SMM) and perceived pricing on consumers' repurchase intentions, with trust serving as a mediating factor, in the context of modern retail outlets in Padang City. A quantitative method was utilized, employing Partial Least Squares–Structural Equation Modeling (PLS-SEM) for data analysis. Data were obtained through questionnaires administered to 250 participants, all of whom were patrons of Budiman Swalayan. The analysis revealed that both SMM and price perception have a positive and significant influence on customer trust. Moreover, price perception has a direct and essential effect on repurchase intention, whereas SMM does not exhibit a substantial direct effect on repurchase intention. Trust demonstrated a significant impact on repurchase intention and was confirmed as a significant mediator in the relationship between both SMM and price perception with repurchase intention. These outcomes highlight the crucial role of trust in connecting SMM and pricing perceptions to consumer loyalty. From a practical standpoint, the study emphasizes the necessity of consistent digital marketing efforts and equitable pricing strategies as fundamental drivers for building trust and encouraging repeat purchases.